Lichen Aureus : Atypcial Presentation Showing Remarkable Therapeutic Response - Kaur Charandeep; kaur Sukhjot; Thami G . P; Kanwar A . J (Wolters Kluwer Medknow Publications, 2002)
A typical patient with zosteriform distribution of rust-coloured to yellowish brown patches over the right leg is reported. The histopathology was consistent with lichen aureus.